(untitled) (Journal of the College of Basic Education, 2022)
The field experiment was conducted at the Botanical Garden at the Department of Biology, College of Education of Pure Sciences (Ibn Al-Haitham), University of Baghdad and during the winter agricultural season 2019-2020 to study the effect of glutathione application at concentration of 0, 50, 100 mg.L-1 and zinc oxide nanoparticles at concentration 0, 500, 1000 mg.L-1 as well as their interaction in some of the vegetative characterstics of the faba bean plant exposed to different salinity concentrations 0, 5, 10,15 dS.m-1. The results showed a significant increase in the level of plant height, number of leaves, stem diameter, number of nodes when treated with glutathione, particularly concentration of 100 mg.L-1, as well as a significant increase in the mean characteristic of plant height, stem diameter and number of nodes when treated with zinc oxide nanoparticles, particularly at concentration 1000 mg.L-1, the plant’s exposure to different concentrations of NaCl led to a significant decrease in the mean plant height, number of leaves, nodes, stem diameter, especially at the salinity concentration 15 dS.M-1, while the treatment with glutathione, zinc oxide nanoparticles and different concentration from NaCl did not appear significant effect in the mean characteristic of the plant branches number. The duel and triple interactions recorded significant effect on the most characteristics.